2005
DOI: 10.1055/s-2005-923538
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of Primary Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH), which constitutes 10 to 15% of all strokes and affects approximately 65,000 people each year in the United States, has the highest mortality rate of all stroke subtypes. Hypertension, cerebral amyloid angiopathy, and anticoagulation underlie the majority of cases of ICH. Warfarin not only increases the risk but also increases the severity of ICH by causing hematoma expansion. With the advent of gradient-echo magnetic resonance imaging, patients with underlying cerebral amyloid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…T2*-weighted MR microscopy can be readily applied to screening all A␤-targeted immunotherapeutics in a longitudinal manner. This methodology can also be used in the evaluation of compounds directly targeting CAA, which is a disorder of growing societal importance and with few therapeutic options (Towfighi et al, 2005). Therefore, the information generated using this technology has the potential to directly translate to human clinical trials and thus may accelerate drug innovation.…”
Section: Discussionmentioning
confidence: 99%
“…T2*-weighted MR microscopy can be readily applied to screening all A␤-targeted immunotherapeutics in a longitudinal manner. This methodology can also be used in the evaluation of compounds directly targeting CAA, which is a disorder of growing societal importance and with few therapeutic options (Towfighi et al, 2005). Therefore, the information generated using this technology has the potential to directly translate to human clinical trials and thus may accelerate drug innovation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of survivors suffer long-term neurologic deficits and are unable to return to independent levels of function [1]. While hematoma formation causes injury by multiple mechanisms [5][6][7][8], the most significant factor influencing outcome is mass effect from the hematoma itself [9,10]. Therefore, interventions that minimize ongoing bleeding are likely to be critical for improving outcomes.…”
Section: Intracerebral Hemorrhage: Hematoma Formation and Expansionmentioning
confidence: 98%
“…This finding raises a new safety concern that may be relevant to humans because ∼90% of human AD patients have concomitant CAA, and similar intracranial hemorrhages were seen in one actively vaccinated patient (Ferrer et al 2004). Most of these hemorrhages were small, and the clinical significance of these microbleeds is not entirely certain; they can be found frequently in asymptomatic patients with CAA (Towfighi et al 2005). Likewise, one preclinical passive vaccination study reported that although there were larger numbers of microhemorrhages and worsening CAA in antibody-treated mice, these did not negate the generally positive effects of treatment on behavioral performance (Wilcock et al 2004b).…”
Section: Passive Aβ Vaccination In Transgenic Mice Modeling Aspects Omentioning
confidence: 99%